Evolution of Sangiovese Wines With Varied Tannin and Anthocyanin Ratios During Oxidative Aging - Gambuti, Angelita; Picariello, Luigi; Rinaldi, Alessandra; Moio, Luigi (Frontiers in Chemistry, 2018)
Changes in phenolic compounds, chromatic characteristics, acetaldehyde, and protein-reactive tannins associated with oxidative aging were studied in Sangiovese wines with varied tannin T/anthocyanin A ratios. For this purpose, three Sangiovese vineyards located in Tuscany were considered in the 2016 vintage. To obtain wines with different T/A ratios, two red wines were produced from each vinification batch: a free run juice with a lower T/A ratio and a marc pressed wine with a higher T/A ratio. An overall of 6 wines with T/A ratios ranging between 5 and 23 were produced. An oxidation treatment (four saturation cycles) was applied to each wine. Average and initial oxygen consumption rates (OCR) were positively correlated to VRF/mA (vanilline reactive flavans/monomeric anthocyanins) and T/A ratios while OCRs were negatively related to the wine content in monomeric and total anthocyanins. The higher the A content was, the greater the loss of total and free anthocyanins. A significant lower production of polymeric pigments was detected in all pressed wines with respect to the correspondant free run one. A gradual decrease of tannin reactivity towards saliva proteins after the application of oxygen saturation cycles was detected. The results obtained in this experiment indicate that VRF/mA and T/A ratios are among the fundamental parameters to evaluate before choosing the antioxidant protection to be used and the right oxidation level to apply for a longer shelf-life of red wine.